Experimental and Numerical Investigation of Welding Residual Stress of U-Rib Joints in Orthotropic Steel Bridge Decks - Zhiqiang Huang; Wenxue Su; Jun Shi; Tao Li; Hongyou Cao (Buildings, 2025)
The residual stresses at U-rib joints have a significant adverse impact on the structure. Therefore, it is necessary to conduct research and analysis on their residual stresses. Based on experimental testing and thermal elastic-plastic finite element analysis (FEA), this study investigates the residual stress (RS) of a U-rib joint using gas metal arc welding in an orthotropic steel bridge deck (OSBD). X-ray diffraction (XRD) was adopted to measure the RS of the U-rib welds, and the measurement results were utilized to verify the FEA. The effects of the weld root gap, weld penetration, and weld groove angle on the RS of U-rib welds were investigated by using FEA. The weld root gap had minor effect on the RS of the U-rib welds. With an increase in weld penetration, the peak values of the transverse tensile RS at both the deck plate and the U-rib weld toes increased. Additionally, an enlargement of the groove angle also resulted in a notable increase in the transverse tensile RS peak at the deck plate weld toe.